TEXT-BASED CMC ON THESIS SUPERVISION THROUGH WHATSAPP IN PANDEMIC ERA - Palupi Palupi; Lulu Adzizah Febrianti (Universitas Darussalam Gontor collaboration with ISKI (Ikatan Sarjana Ilmu Komunikasi Indo, 2021)
The learning and teaching processes have shifted from offline to online during Covid-19 pandemic. Online platforms are used to support learning and teaching process from early childhood to higher education institution. Another process that is important in the teaching and learning process in universities is the process of thesis supervision which before the pandemic used to be held face-to-face. Lecturers and students of the Department of Communication Science, Universitas Muhammadiyah Surakarta use WhatsApp as a text-based CMC platform in conducting thesis supervision. Text-based CMC is lack of nonverbal and visual experiences compared to face-to-face communication (Walther, 1996). This research aim is to understand how CMC perspectives are developed between thesis supervisors and their students in thesis supervision process using WhatsApp. A descriptive qualitative research method was used in this study involving 3 thesis supervisors and 3 students as informants. Semi-structured interview was used to collect data. The results showed that the communication perspective in the thesis supervision process through WhatsApp are: (1) impersonal, indicated by the lack of nonverbal cues, delayed feedback, lack of conversational language, and focus distracted. (2) Interpersonal, indicated by the time of interaction, motivation, and the use of emoticons, and (3) hyperpersonal, indicated by online presentation management.